Preventing type 1 diabetes in late-stage pre-diabetic NOD mice with insulin: A central role for alum as adjuvant - Martens, Pieter-Jan; Ellis, Darcy; Bruggeman, Ylke; Viaene, Marijke; Laureys, Jos; Teyton, Luc; Mathieu, Chantal; Gysemans, Conny (Frontiers in Endocrinology, 2022)
Background. Restoration of immune tolerance to disease-relevant antigens is an appealing approach to prevent or arrest an organ-specific autoimmune disease like type 1 diabetes (T1D). Numerous studies have identified insulin as a key antigen of interest to use in such strategies, but to date, the success of these interventions in humans has been inconsistent. The efficacy of antigen-specific immunotherapy may be enhanced by optimising the dose, timing, and route of administration, and perhaps by the inclusion of adjuvants like alum. The aim of our study was to evaluate the effect of an insulin peptide vaccine formulated with alum to prevent T1D development in female non-obese diabetic (NOD) mice when administered during late-stage pre-diabetes. Methods. Starting at 10 weeks of age, female NOD mice received four weekly subcutaneous injections of an insulin B:8-24 (InsB:8-24) peptide with (Ins+alum) or without Imject® alum (Ins) as adjuvant. Diabetes incidence was assessed for up to 30 weeks of age. Insulin autoantibodies and C-peptide concentrations were measured in plasma and flow cytometric analysis was performed on pancreatic-draining lymph nodes (PLN) and pancreas using an InsB:12-20-reactive tetramer. Results. InsB:8-24 peptide formulated in alum reduced diabetes incidence (39%), compared to mice receiving the InsB:8-24 peptide without alum (71%, P < 0.05), mice receiving alum alone (76%, P < 0.01), or mice left untreated (70%, P < 0.01). This was accompanied by reduced insulitis severity, and preservation of C-peptide. Ins+alum reduced the frequencies of pathogenic effector memory CD4+ and CD8+ T cells in the pancreas and increased the frequency of insulin-reactive FoxP3+ Tregs in the PLN. Of interest, insulin-reactive Tregs were enriched amongst populations of Tregs expressing markers indicative of stable FoxP3 expression and enhanced suppressive function. Conclusion. An InsB:8-24 peptide vaccine, but only when formulated in alum, prevented the onset of T1D in late-stage pre-diabetic NOD mice and reduced the activation of pathogenic CD4+ and CD8+ T cells.